A retrospective analysis of electrical burn injuries - Kamble, Pravin B.; Kshirsagar, Hemant S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Our life is running at a fast pace holding hands of the hi-tech innovations in this ever-developing scenario. Electricity runs the show of the whole technology is potentially dangerous commodity to handle in daily life. Hence, electric burn injuries have been a public health threat. Electrical burns are less prevalent but are the most disastrous. Electrical burn injuries are considered as a unique form of trauma where in morbidity and mortality rates are much higher compared to the other thermal burns. This study is a retrospective analysis of electrical burn injuries that provides an insight to all facts regarding the electric burn injuries. Methods: This paper is structured upon the patients with electrical burn injuries who were admitted to the hospital. The medical data of all burn patients admitted to our hospital between March 2011 to January 2023 were evaluated for inclusion. Incusion criteria were age 18 years old and above. The patients were divided into two age groups: 18-45 years as younger age and above 45 years old as elder age. Results: Out of 82 occurrences of electrical burns caused by workplace dangers, 80 involved men. Male patients ranging age from 18 to above 45 years were present, 12 adults above the age of 45 years were there. Accidental electric shocks caused by low-voltage home appliances struck two elderly patients and two female patients. Conclusions: The cause of electrical burn incidences was work related. The common patient population was consisted of electrical- mechanical workers, industrial workers, agriculture field worker, and construction workers.